1997
DOI: 10.1007/pl00009683
|View full text |Cite
|
Sign up to set email alerts
|

The effects of propagation environment and foliar area on the rooting physiology of Cordia alliodora (Ruiz & Pavon) Oken cuttings

Abstract: AbstractmThe effects of propagation microclimate and foliar area on the rooting of Cordia alliodora (Ruiz & Pavon) Oken cuttings were investigated using non-mist propagators with and without shade. Photosynthetic rates (Pn), stomatal conductance (gs) and chlorophyll fluorescence ratio (Fv/Fm) of the cuttings were assessed during propagation. Pronounced differences in microclimate were recorded between treatments, with lower temperatures and vapour pressure deficit (VPD) under shade. During the first 8 days aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 13 publications
3
16
1
Order By: Relevance
“…Our results showed that cuttings under mist irrigation can be prone to long periods of moderate photoinhibition (F V /F M mostly >0.65) and yet remain highly capable of root production. These findings contrast with results from cuttings of other species placed in unshaded nonmist propagators, in which more severe photoinhibition develops (F V /F M <0.60), and rooting percentages decline with decreasing F V /F M (Mesén et al 1997(Mesén et al , 2001. Photoinhibition could be partially alleviated by lowering irradiance or by applying foliar fertiliser.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…Our results showed that cuttings under mist irrigation can be prone to long periods of moderate photoinhibition (F V /F M mostly >0.65) and yet remain highly capable of root production. These findings contrast with results from cuttings of other species placed in unshaded nonmist propagators, in which more severe photoinhibition develops (F V /F M <0.60), and rooting percentages decline with decreasing F V /F M (Mesén et al 1997(Mesén et al , 2001. Photoinhibition could be partially alleviated by lowering irradiance or by applying foliar fertiliser.…”
Section: Discussioncontrasting
confidence: 72%
“…Photoinhibition could be partially alleviated by lowering irradiance or by applying foliar fertiliser. Reduced irradiance in the propagation environment has been used to minimise photoinhibition (Mesén et al 1997) and increase rooting percentages of cuttings from other tree species (Aminah et al 1997a;Mesén et al 1997;Nketiah et al 1998). Cuttings without roots are prone to nutrient leaching and nutrient deficiencies during extended periods under mist irrigation, as uptake of nutrients through the base of cuttings from the propagation medium is generally very low (Blazich 1988;Hartmann et al 1997).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The effect of nutrient status on rooting has been studied during adventitious root development in leafy cuttings (Dick and Dewar 1992). The accumulation of starch at the cutting bases in avocado improves its rooting capability (Reuveni and Raviv 1980), although starch-filled cuttings of T. scleroxylon develop very poor rooting due to inhibited post-severance photosynthesis (Leakey and Coutts 1989;Leakey and Storeton-West 1992;Mesén et al 1997Mesén et al , 2001. The third factor is the lower elemental content of N, P, and K in large cuttings (Burgess et al 1990), which is negatively correlated with rooting.…”
Section: Discussionmentioning
confidence: 99%